2018
DOI: 10.1021/acsomega.8b02556
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Highly Stable Pd@CeO2 Catalyst for Methane Combustion with the Synergistic Effect of Urea and Citric Acid

Abstract: Making use of synergy between urea and citric acid, a core–shell Pd@CeO 2 catalyst with spherical morphology was facilely synthesized by a hydrothermal method. The formation mechanism of the core–shell structure in the presence of citric acid and hydrogen peroxide was studied. Results showed that the Pd@CeO 2 catalyst exhibited high catalytic activity in methane oxidation. Pd nanoparticles were well stabilized by CeO 2 shell encapsulation, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…20 The intensity of the LT peak increases significantly in the order Al 2 O 3 < ZrO 2 < CeO 2 accompanied by a shift of its maximum from 78 to 94 °C, indicating that the number and strength of basic sites increases following the above order. 20,21 The total amount of desorbed CO 2 was estimated from the area below the CO 2 response curve and was found equal to 45 μmol/g for Al 2 O 3 , 100 μmol/g for ZrO 2 , and 144 μmol/g for CeO 2 , which further confirmed the higher basicity of CeO 2 compared to ZrO 2 and Al 2 O 3 in accordance to previous studies. 22 It has been reported that metal oxides are generally characterized by two types of basic sites, the basic hydroxyl groups and basic surface oxygen, where CO 2 can be adsorbed resulting in carbonates and bicarbonates production.…”
Section: Resultssupporting
confidence: 87%
“…20 The intensity of the LT peak increases significantly in the order Al 2 O 3 < ZrO 2 < CeO 2 accompanied by a shift of its maximum from 78 to 94 °C, indicating that the number and strength of basic sites increases following the above order. 20,21 The total amount of desorbed CO 2 was estimated from the area below the CO 2 response curve and was found equal to 45 μmol/g for Al 2 O 3 , 100 μmol/g for ZrO 2 , and 144 μmol/g for CeO 2 , which further confirmed the higher basicity of CeO 2 compared to ZrO 2 and Al 2 O 3 in accordance to previous studies. 22 It has been reported that metal oxides are generally characterized by two types of basic sites, the basic hydroxyl groups and basic surface oxygen, where CO 2 can be adsorbed resulting in carbonates and bicarbonates production.…”
Section: Resultssupporting
confidence: 87%
“…The role of ceria on methane oxidation performance in core-shell nanoparticles has been further confirmed by the comparison of Pd@CeO2 with Pd@TiO2 both supported on SiO2/Al2O3, with the latter showing a much lower catalytic activity (~35% methane conversion at 573 K for Pd-Ce system against ~15% conversion for Pd-Ti; CH4/O2 = 2 and GHSV≈170000 ml/(g•h)) [39]. A similar configuration with Pd@CeO2 core-shell units, in this case without support, has been recently described by Cai et al [92]. Ceria shell helps to avoid the aggregation of Pd particles as well as to maintain them in oxidized state.…”
Section: Role Of Ceria On Catalytic Activitysupporting
confidence: 80%
“…For example, in our group we have observed that when the catalyst formulation involves Pd entities embedded into ceria lattice the overall stability in presence of water is very good and higher with respect to the impregnated analogues containing Pd nanoclusters, both in transient and in steady state conditions, the loss in conversion during time on stream experiments being comprised between 10% and 20% against 75% of impregnated catalysts [17,22]. The same does not hold for core-shell Pd@CeO2 units, supported [42] or unsupported [92], for which the formation of stable OH groups on ceria is proposed to inhibit the oxygen exchange with PdO and its accessibility to the gas phase [42]. For the alumina-supported core-shell units an additive deactivation in presence of water and phosphorus has also been observed, and ascribed to the agglomeration of CeO2 nanoparticles with subsequent incorporation of Pd active phase [138].…”
Section: Poisoning and Deactivation Of Pd-based Catalystsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 5b, the Pd/0TA catalyst shows that the reduction peak of finely dispersed PdO is located at 130 °C, which is consistent with the results reported in the literature. 38 The peak appearing at 410 °C is attributed to the reduction of subsurface palladium species, 39 and the broad peak located at 800–900 °C is due to the reduction of bulk oxygen. 40 Notably, the Pd/15TA catalyst exhibits the lowest reduction temperature of PdO (ca.…”
Section: Results and Discussionmentioning
confidence: 99%